2022
DOI: 10.3390/ani12192581
|View full text |Cite
|
Sign up to set email alerts
|

A Novel A > G Polymorphism in the Intron 1 of LCORL Gene Is Significantly Associated with Hide Weight and Body Size in Dezhou Donkey

Abstract: Several studies have shown the association between the ligand-dependent nuclear receptor compression-like protein (LCORL) gene and body size in horses, pigs and donkeys. Based on previous studies, the LCORL gene was hypothesized to be associated with growth traits and hide weight in Dezhou donkeys. In this study, we aimed to reveal the variation of the LCORL gene in the Dezhou donkey and explore whether the gene is associated with hide weight and body size. In this study, genetic polymorphisms in the LCORL gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…An association analysis between different genotypes of an SNP and growth traits was carried out using the general linear model with SPSS 19.0 (IBM, Armonk, NY, USA). The model was: Yij = μ + Gi + eij where Yij represents the observed value of the jth individual of genotype i, μ denotes the mean of the observed values, Gi represents the effective value of the genotype i, and eij denotes the random error [ 24 ]. The significance of differences was tested using Tukey’s multiple-range test.…”
Section: Methodsmentioning
confidence: 99%
“…An association analysis between different genotypes of an SNP and growth traits was carried out using the general linear model with SPSS 19.0 (IBM, Armonk, NY, USA). The model was: Yij = μ + Gi + eij where Yij represents the observed value of the jth individual of genotype i, μ denotes the mean of the observed values, Gi represents the effective value of the genotype i, and eij denotes the random error [ 24 ]. The significance of differences was tested using Tukey’s multiple-range test.…”
Section: Methodsmentioning
confidence: 99%
“…They were both 2-year-old fattening donkeys and lived in standard feeding conditions with the same feeding and management conditions. The 393 donkeys in this study were identified in the same way as the source of the 396 donkeys in “A Novel A > G Polymorphism in the Intron 1 of LCORL Gene Is Significantly Associated with Hide Weight and Body Size in Dezhou Donkey” [ 22 ]. Among them, the NKX1-2 gene was not amplified in three donkeys, so it was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The model structure is Yi = µ + a.i. + e, where Yi is the individual phenotype values, µ is the mean value of each trait in the population, as is the fixed factor genotype, and e is the random error [ 22 ]. Results were presented as Means ± SE.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that certain variants in the myostatin gene were associated with body weight and hip height in donkeys, indicating that the myostatin gene may play a role in determining these traits in donkeys. Moreover, many other genes, such as LTBP2 [85], CDKL5 [86], TBX3 [87], LCORL [88], DCAF7 [89], PRKG2 [90], and HOXC8 [91], as well as their polymorphisms, have been reported to be associated with different meat production phenotypic traits in Dezhou donkeys (Table 2). NCAPG-DCAF16 Donkeys with AA and GA genotypes had significantly higher body weight, body height, and rump height compared to those with the GG genotype at 3 months of age (p < 0.05).…”
Section: Genetic Markers Associated With Growth and Meat Production P...mentioning
confidence: 99%